THE EFFECT OF URBANISATION ON ENVIRONMENT: WITH SPECIAL REFERENCE TO THE CITY OF GUWAHATI, ASSAM - Mehzabeen Sultana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Urbanisation is a process whereby population move from rural to urban area leading to an increase in the number of population living in the towns and cities and thereby further leading to growth and expansion of the towns and cities. Urbanisation is one of the key features of the developing countries. It has both positive as well as negative effects. On one hand urbanisation has provided better health facilities, better educational facilities, and more employment opportunities. On the other hand it has also become a potential threat to our environment as uncontrolled urban population growth has resulted in environmental degradation in the form of increase in the slum areas, worse water quality, excessive air pollution, noise pollution and problems of waste disposal. Urbanisation cannot be restricted as it is considered as an indicator of development but it has to be ensured that it proceeds in the right manner within its appropriate limit, taking proper care of the environment. In this paper an attempt has been made to analyse the effect of urbanisation on environment. The focus of the study is on the city of Guwahati which is one of the largest and fastestgrowing cities of the North-East India. Guwahati has also been the centre of attraction for various commercial and industrial activities due to its favourable geographic location.The pressure of the ever increasing human population and expanding commercial and industrial activities has resulted in significant risks of environmental degradation in the city. Based onsecondary data this paper tries to explain how urbanisation has brought about a situation of trade-off between development and environment protection.